(untitled) (Journal of Medicine, 2023)
Introduction: Robust data of LDH (Lactate dehydrogenase) is available in bacterial infection, and it can be utilized in this COVID-19 Pneumonia pandemic for initial assessment, planning of treatment in indoor setting in association with HRCT severity. Methods: Prospective, observational, 12 weeks follow up study, included 2000 COVID-19cases confirmed with RT PCR. All cases were assessed with lung involvement documented and categorized on HRCT thorax, oxygen saturation, LDH at entry point and follow up. Age, gender, comorbidity and BIPAP/NIV use and outcome as with or without lung fibrosis as per CT severity. Statistical analysis is done by Chi square test. Results: HRCT severity score at entry point has significant correlation with LDH titer [p<0.00001] LDH titer has significant association with duration of illness (Doi) [p<0.00001] Comorbidities has significant association with LDH titer. [p<0.00001] LDH titer has significant association with oxygen saturation [p<0.00001] BIPAP/NIV requirement during hospitalization has significant association with LDH titer. [p<0.00001] Timing of BIPAP/NIV requirement has significant association with LDH titer. [p<0.00001] Follow-up LDH titer during hospitalization as compared to entry point (initial) normal and abnormal LDH has significant association in post-covid lung fibrosis [p<0.00001] Conclusion: LDH is easily available, and universally acceptable inflammatory marker in COVID-19 pandemic and documented very crucial role in covid-19 pneumonia in predicting severity of illness, assessing response to treatment and analyzing outcome during hospitalization. J MEDICINE 2023; 24: 10-17